2017
DOI: 10.1002/ece3.3501
|View full text |Cite
|
Sign up to set email alerts
|

Broadening the voice of science: Promoting scientific communication in the undergraduate classroom

Abstract: Effective and accurate communication of scientific findings is essential. Unfortunately, scientists are not always well trained in how to best communicate their results with other scientists nor do all appreciate the importance of speaking with the public. Here, we provide an example of how the development of oral communication skills can be integrated with research experiences at the undergraduate level. We describe our experiences developing, running, and evaluating a course for undergraduates that complemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…We recommend that opportunities for training in both technical and nontechnical science communication be ubiquitous for plant scientists. We encourage universities to require science communication more frequently in undergraduate curricula (Cirino et al., 2017; Hoffmann‐Longtin, 2019) even when such communication might seem to be a peripheral skill at that stage. If this training is successfully implemented, budding scientists will become spokespeople calling attention to the relevance of plant science to people's lives and its nearly limitless potential to improve them.…”
Section: Recommendationsmentioning
confidence: 99%
“…We recommend that opportunities for training in both technical and nontechnical science communication be ubiquitous for plant scientists. We encourage universities to require science communication more frequently in undergraduate curricula (Cirino et al., 2017; Hoffmann‐Longtin, 2019) even when such communication might seem to be a peripheral skill at that stage. If this training is successfully implemented, budding scientists will become spokespeople calling attention to the relevance of plant science to people's lives and its nearly limitless potential to improve them.…”
Section: Recommendationsmentioning
confidence: 99%
“…Through colloquial and conference presentations, as well as manuscript writing, undergraduate researchers in statistics gain experience in communicating results that is not generally a primary component of standard coursework. Several researchers have stressed the importance of integrating training in science communication into the URE (Hensel 2012;Cirino et al 2017), and Denofrio et al (2007) reported success in student perceived gains in oral communication from a CURE. • S5: Confidence as a statistician (12 responses).…”
Section: Benefits To Studentsmentioning
confidence: 99%
“…A range of different in-class strategies are used to embed these skills alongside science literacy and research training, e.g. using peer postgraduate student co-instructors to intensively train undergraduates to bolster their confidence in their oral communicative abilities (Cirino et al, 2017). Within our division, however, postgraduate students are not employed for teaching, learning and assessment purposes so we could not seek their support.…”
Section: Developing Science Communication Skillsthe Contextmentioning
confidence: 99%